Treatment options for patients with brain metastases from EGFR/ALK-driven lung cancer. Issue 2 (May 2017) - Doherty, Mark K.; Korpanty, Grzegorz J.; Tomasini, Pascale; Alizadeh, Moein; Jao, Kevin; Labbé, Catherine; Mascaux, Celine M.; Martin, Petra; Kamel-Reid, Suzanne; Tsao, Ming-Sound; Pintilie, Melania; Liu, Geoffrey; et al.
Abstract: Introduction: Brain metastases in EGFR / ALK -driven NSCLC frequently pose treatment dilemmas. Tyrosine kinase inhibitors (TKIs) can control extracranial disease, but radiotherapy is often required for intracranial control. We aimed to evaluate the impact of first-line whole brain radiotherapy (WBRT), stereotactic radiotherapy (SRS) or TKI alone on outcomes of patients with brain metastases from EGFR / ALK -driven NSCLC. Methods: This single center retrospective review included 184 patients with brain metastases from EGFR / ALK -driven NSCLC, and analyzed effect of treatment choice on time to intracranial progression (TTIP) and overall survival (OS). Results: First-line treatment for brain metastases consisted of WBRT in 120 patients, SRS in 37 and TKI alone in 27. WBRT-treated patients had more brain metastases, and more baseline symptoms. Median TTIP was longer in the WBRT group at 50.5 months than SRS or TKI groups at 12 and 15 months ( p  = 0.0038). No significant difference was seen in median OS: 21.6 months in the WBRT group, 23.9 months in the SRS group and 22.6 months in the TKI group ( p  = 0.67). In multivariable analysis, age > 65 years (HR 2.2, p  = 0.0014), greater number of brain metastases (HR 2.48, p  = 0.0002) and greater number of extracranial metastatic sites (2 vs 0–1 HR = 2.05, p  = 0.014 and 3+ vs 0–1 HR = 2.95, p  = 0.0001 were associated with shorter OS. No independent effect was seen from first-line CNS treatment choice. Conclusions: First-line WBRT for brain metastases from EGFR / ALK -driven NSCLC was associated with longer TTIP than SRS or TKI alone, with no difference in OS. These results could support deferral of WBRT until intracranial progression in selected patients who are closely monitored.